Relato de experiência do ensino da Filosofia no município de Pacatuba - Ceará: práticas exitosas desenvolvidas no 9º ano da escola professora Maria Mirtes Holanda do Vale - Rivellini, Maria de Fatima de Oliveira Silva (2024)
The teaching of philosophy is one of the most effective ways to develop more critical and engaged individuals, and its early introduction is increasingly advocated. By working with this subject, we help build people capable of thinking independently, without being influenced by false information or common sense. Currently, philosophy education is only mandatory from the first year of high school, and with rare exceptions, students only come into contact with this subject for three years during their basic education. Several authors, including Matthew Lipman, Walter Kohan, and Paulo Freire, advocate for the inclusion of philosophy as early as possible in basic education. These authors, therefore, serve as the foundation for the discussions in this dissertation. From this perspective, the municipality of Pacatuba, located in the metropolitan region of Fortaleza, stands out as one of the pioneers in offering this subject to the final years of elementary school, demonstrating its understanding of the importance of philosophy. The methodology of this work classifies it as an experience report, presenting lessons developed throughout the 2023 school year for 9th-grade classes. Each of these lessons is presented and contextualized, explaining the theme addressed, the skill that was worked on according to the municipality's curriculum framework, the time required for the lesson, an explanation of the activity, and the observed results. A total of 20 lessons are presented. The overall objective of the work is to showcase successful practices developed in two 9th-grade classes at the Professora Maria Mirtes Holanda do Vale Elementary School. By the end of the project, it was evident that students, who were initially resistant to the activities, gradually understood them and became increasingly interested in participating autonomously. As a result, by the end of the project, a proposal for an elective course focused on the teaching of philosophy was created, with the aim of further valuing this formative subject.